Implementasi Kurikulum Merdeka di Sekolah Dasar: Studi Kasus di SDN 106813 Amplas - Muthia Rahma; Nayla Sufina Muslim Hutagalung; Nur Aulia Heriani; Fatmadani Siregar (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to analyze the implementation of the Independent Curriculum at SDN 106813 Amplas, focusing on the implementation by lower and upper grade teachers, the obstacles faced, and the strategies used to overcome these challenges. The research method used is qualitative with a case study approach. Data were collected through interviews, observations, and documentation. The results of the study indicate that lower grade teachers use more exploration and game- based approaches, while upper grade teachers apply project- based learning and problem solving. The main obstacles in implementing this curriculum are the lack of training for teachers, limited facilities and infrastructure, and difficulties in formative assessment and differentiated learning. The strategies implemented include strengthening training, utilizing technology in learning, and collaboration between teachers, students, and parents. This study suggests further support from schools and the government in the form of intensive training and providing adequate facilities.